Review of the species of the genus Marthogryllacris (Orthoptera, Gryllacrididae, Gryllacridinae) - Li, Miaomiao; Fang, Yan; Liu, Xianwei; Li, Kai (Zootaxa, 2014)
A review of the genus Marthogryllacris Karny, 1937 was presented. The genus Borneogryllacris should be regarded as a subgenus of Marthogryllacris. Five new species were described: M. (M.) rufonotata sp. nov., M. (B.) nanlingensis sp. nov., M. (B.) bimaculata sp. nov., M. (B.) spinosa sp. nov. and M. (B.) elongata sp. nov.. A key to the species of Marthogryllacris and the distributional data were provided.